2022
DOI: 10.1073/pnas.2122090119
|View full text |Cite
|
Sign up to set email alerts
|

Lack of association between pandemic chilblains and SARS-CoV-2 infection

Abstract: An increased incidence of chilblains has been observed during the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) pandemic and attributed to viral infection. Direct evidence of this relationship has been limited, however, as most cases do not have molecular evidence of prior SARS-CoV-2 infection with PCR or antibodies. We enrolled a cohort of 23 patients who were diagnosed and managed as having SARS-CoV-2–associated skin eruptions (including 21 pandemic chilblains [PC]) during the first wave of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 52 publications
0
18
0
Order By: Relevance
“…Long et al ., 2020; Seow et al ., 2020; Ward, Cooke, et al ., 2020; Choe et al ., 2021), single timepoint serology estimates may yield misleading insights into the true extent of CoV2 spread. We, therefore, aimed to investigate the evolution of the CoV2 seroprevalence in the canton of Zurich, a particularly low prevalence setting during the first and second waves in 2020, using an in-house developed tripartite automated blood immunoassay (TRABI) already employed in multiple studies (Cervia et al ., 2020; Emmenegger, Saseendran Kumar, et al ., 2021; Emmenegger et al ., 2022; Gehlhausen et al ., 2022; Schneider et al ., 2022). Continuous immunosurveys were conducted in a large cohort of the University Hospital of Zurich (n=55’814 samples) and blood donors from the Blood Donation Services of the canton of Zurich (n=16’291), over a period from December 2019 to December 2020, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Long et al ., 2020; Seow et al ., 2020; Ward, Cooke, et al ., 2020; Choe et al ., 2021), single timepoint serology estimates may yield misleading insights into the true extent of CoV2 spread. We, therefore, aimed to investigate the evolution of the CoV2 seroprevalence in the canton of Zurich, a particularly low prevalence setting during the first and second waves in 2020, using an in-house developed tripartite automated blood immunoassay (TRABI) already employed in multiple studies (Cervia et al ., 2020; Emmenegger, Saseendran Kumar, et al ., 2021; Emmenegger et al ., 2022; Gehlhausen et al ., 2022; Schneider et al ., 2022). Continuous immunosurveys were conducted in a large cohort of the University Hospital of Zurich (n=55’814 samples) and blood donors from the Blood Donation Services of the canton of Zurich (n=16’291), over a period from December 2019 to December 2020, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…This conspicuous vascular damage explains why some authors initially included chilblains in the group of acral livedoid lesions, even though they develop in patients with a different background and prognosis [ 7 ]. Interestingly, despite the marked increase in reporting and severity of chilblain cases during the pandemic, an epidemiological correlation between serologically demonstrated COVID-19 infection and chilblains has never been statistically demonstrated [ 8 ]. The most feasible explanation is that after contact with the virus, the robust innate responses of younger individuals lead to abortive seronegative infections.…”
Section: Distinctive Covid-19-associated Inflammatory Dermatitismentioning
confidence: 99%
“…Most of the cases occur in younger people with no supporting evidence of covid infection. A recent study1 made a detailed analysis of 21 cases in Connecticut and found that 19 had no immunological evidence of a past SARS-CoV-2 specific infection. It concludes the condition may be unrelated to coronavirus.…”
Section: Have Researchers Finally Nailed What’s Been Going On?mentioning
confidence: 99%